A case-control study and meta-analysis of the association of eNOS rs1799983 SNP with stroke risk - Phneh, KY; Chong, ETJ; Sybil Shah S,; Chia, YK; AG. Daud DM,; Jalil E,; Cheng, KCS; Lee, PC (Pusat Perubatan Universiti Kebangsaan Malaysia, 2019)
The endothelial nitric oxide synthase (eNOS) rs1799983 polymorphism is known to increase the risk towards stroke, but data is under-reported in Malaysian population. Therefore, this study sought to investigate this association in a Malaysian population and in a comprehensive meta-analysis. Genotyping of the eNOS rs1799983 polymorphism was performed for 241 Malaysians using a hydrolysis probe. Odd ratio with 95% confidence interval was calculated. Meta-analysis was conducted using the Comprehensive Meta-Analysis software ver. 2.2.064. A p-value less than 0.05 was considered statistically significant. Overall, our results showed that the presence of eNOS rs1799983-T allele increases the risk towards stroke, particularly in males, fast-food goers and Malaysian Chinese. The meta-analysis showed that the rs1799983 polymorphism is significantly associated with an increase ischemic stroke risk in the recessive and allelic models. After stratified with population, these associations remain significant in the Asian population but not in the Caucasian population. In summary, this study establishes a significant relationship between the eNOS rs1799983 polymorphism with gender, lifestyle and ethnicity differences towards stroke risk in the Malaysian population. In addition, our meta-analysis suggests that the eNOS rs1799983 polymorphism is associated with an increase risk of ischemic stroke.